International Human Right and Islamic Law: Sebuah Upaya Menuntaskan Wacana-Wacana Kemanusiaan - Febri Hijroh Mukhis (IAIN Ponorogo, 2017)
Abstract: Islam brings universal messages involve justice, equality, respect and humanity. These actually are the sacred Sunnah of the Prophet. However, the current problems of human are so varied, in line with the development of information and technology which are so advanced. Those problems could be positive if everyone really understands the universal messages of Prophet by always on the side of social-humanity. This article seeks to examine the problem of human rights and Islamic law as the one of efforts to resolve the dichotomy between Islam and the humanity problems. This article is the conceptual study which specifically uses qualitative descriptive study. The conclusion of this study is the dichotomy between the concept of human rights and Islamic law must be resolved, both are on one purpose involve justice, equality and humanity. Human right is a common concern regardless of any interest, whether religious, politic, culture, and even science. If there is no harmony in the concept of humanity in a religious frame or tauhid, then the understanding of humanity must be freed from all forms of identity of interests.Abstrak: Islam membawa pesan universal yang abadi, yakni: keadilan, persamaan, penghargaan, dan kemanusiaan. Pesan universal inilah yang sebenarnya Sunnah Nabi yang suci. Namun problem terkini umat manusia begitu variatif, dengan semakin majunya informasi dan teknologi. Problem tersebut bisa menjadi positif jika semua orang benar-benar memahami pesan universal kenabian dengan selalu memihak kepada sosial-kemanusiaan. Artikel ini berupaya mengkaji problem HAM dan hukum Islam sebagai salah satu upaya untuk mengakhiri dikotomi antara Islam dan problem kemanusiaan. Artikel ini merupakan kajian konseptual, dengan jenis kajian kualitatif deskriptif. Kesimpulan dari kajian ini yaitu, dikotomi antara konsep HAM dan hukum Islam haruslah dituntaskan, kedunya berada pada satu ujung tujuan, yakni keadilan, kesetaraan dan kemanusiaan. Urusan kemanusiaan adalah urusan bersama tanpa memandang kepentingan apapun, baik agama, politik, budaya, bahkan pengetahuan. Jika tidak adanya keharmonisan dan kesepahaman antara konsep kemanusiaan dalam bingkai keagamaan atau tauhid maka pemahaman tentang kemanusiaan haruslah dibebaskan dari segala bentuk kepentingan identitas.